THE EFFECTIVENESS OF START WITH SIMPLE STORIES TOWARDTHE STUDENTS’ READING COMPREHENSION OF TENTH GRADE AT SMAN 1 OGODEIDE - Diyenti Rusdin (Universitas Madako Tolitoli, 2018)
This research was pre-experimental research design that aims to find out whether the use of SSS ( Start Simple Stories ) in teaching reading can motivate students reading comprehension of the Tenth Grade at Sma Negeri 1 Ogodeide. The subject of this research was the students of the Tenth Grade at Sma Negeri 1 Ogodeide 2016/2017 academic year which consists of 26 students. The researcher analized the data statically, the result of the test showed that the students’ mean score in post-test 75,65 is high than pre-test 50,3., To know the significant difference between pre-test and post-test, the researcher compared the value of t-counted and t-table by applying 0,05 level of significant for one – tailed test with 25 degree of freedom (26-1 = 25), the researcher found that the t-table 2,060, it means that the t-counted (24,395) was high than t-table (2.060) and the hypothesis of this research was accepted. The researcher concluded that applying SSS (Start Simple Stories) toward the students’ reading comprehension of the Tenth grade at SmaNegeri 1 Ogodeide was effective. .Key Word : Effectiveness, Simple Stories, Reading Comprehesion.